Effect of a 2+1 schedule of ten-valent versus 13-valent pneumococcal conjugate vaccine on pneumococcal carriage: Results from a randomised controlled trial in Vietnam. Issue 16 (15th April 2021) - Temple, Beth; Nation, Monica Larissa; Dai, Vo Thi Trang; Beissbarth, Jemima; Bright, Kathryn; Dunne, Eileen Margaret; Hinds, Jason; Hoan, Pham Thi; Lai, Jana; Nguyen, Cattram Duong; Ortika, Belinda Daniela; Phan, Thanh V.; et al.
Highlights: 1st study to directly compare effect of 2+1 schedule of PCV10 or PCV13 on carriage. Includes an unvaccinated comparator group. Both PCVs reduce carriage of serotypes in the corresponding vaccine. May be some differences between the vaccines in their impact on carriage. Majority of carriage was vaccine-type, so both vaccines likely to be beneficial. Abstract: Background: Pneumococcal conjugate vaccines (PCVs) generate herd protection by reducing nasopharyngeal (NP) carriage. Two PCVs, PCV10 and PCV13, have been in use for over a decade, yet there are few data comparing their impact on carriage. Here we report their effect on carriage in a 2+1 schedule, compared with each other and with unvaccinated controls. Methods: Data from four groups within a parallel, open-label randomised controlled trial in Ho Chi Minh City contribute to this article. Three groups were randomised to receive a 2+1 schedule of PCV10 (n = 250), a 2+1 schedule of PCV13 (n = 251), or two doses of PCV10 at 18 and 24 months (controls, n = 197). An additional group (n = 199) was recruited at 18 months to serve as controls from 18 to 24 months. NP swabs collected at 2, 6, 9, 12, 18, and 24 months were analysed (blinded) for pneumococcal carriage. This study aimed to determine if PCV10 and PCV13 have a differential effect on pneumococcal carriage, a secondary outcome of the trial. We also describe the serotype distribution among unvaccinated participants. Trial registration: ClinicalTrials.gov NCT01953510. Findings: Compared with unvaccinated controls, a 2+1 schedule of PCV10 reduced PCV10-type carriage by 45–62% from pre-booster through to 24 months of age, and a 2+1 schedule of PCV13 reduced PCV13-type carriage by 36–49% at 12 and 18 months of age. Compared directly with each other, there were few differences between the vaccines in their impact on carriage. Vaccine serotypes accounted for the majority of carriage in unvaccinated participants. Interpretation: Both PCV10 and PCV13 reduce the carriage of pneumococcal vaccine serotypes. The introduction of either vaccine would have the potential to generate significant herd protection in this population. Funding: National Health and Medical Research Council of Australia, Bill & Melinda Gates Foundation.